Chemical composition, antibacterial and repellent activities of Azorella trifurcata, Senecio pogonias, and Senecio oreophyton essential oils - López, Sandra Beatriz (2014)
The antibacterial and insect-repellent activities of the essential oils (EOs) from Argentinian medicinal plants Azorella trifurcata (Gaertn.) Pers., Senecio cfr. oreophyton J. Remy and Senecio cfr. pogonias Cabrera, were investigated. All EOs showed good repellent properties against Triatoma infestans Klug, the vector of the Chagas disease, with percent repellence values between 60% and 70% at 24 hours compared with positive control N-N diethyl-m-methylbenzamide (DEET) and moderate activity against the bacteria tested with minimum inhibitory concentrations (MICs) values between 31.2 and 2000 μg/ml. The Azorella trifurcata, Senecio pogonias and S. oreophyton EOs, obtained by hydrodistillation, were characterized by GC-FID and GC/MS analyses. Spathulenol (38.2%), myrtenyl acetate (8.4%) and α-terpineol (4.5%), limonene (9.8%) and α-thujene (5.4%) were the main constituents in the EO of Azorella trifurcata. The Senecio pogonias and S. oreophyton EOs are characterized by a high content of monoterpenes hydrocarbons (92% and 95.1%, respectively) with α-pinene, the main component in both oils. To our knowledge, the essential oil composition from Andean medicinal plants A. trifurcata, Senecio pogonias and S. oreophyton collected in central Andean slopes are reported for first time.